Validitas Dan Reliabilitas Skala Displin Diri Untuk Siswa Sekolah Menengah Pertama - Arofah, Laelatul (Universitas Nusantara PGRI Kediri, 2021)
Self-discipline is one of the characters that must be mastered by students. Individuals who have self-discipline will easily organize, direct, and control everything they do to achieve the desired goals. Conversely, individuals who lack self-discipline will have an impact on students' academic problems. To be able to find out how much self-discipline each individual has, an instrument in the form of a psychological scale of self-discipline is needed. Through this self-discipline scale it is expected to map how high the level of self-discipline of junior high school students is. This study aims to determine the validity and reliability of junior high school students' self-discipline scale. The development of a self-discipline scale uses the steps of arranging an instrument from Riduwan (2013: 32) which consists of six steps. Based on calculations using product moment correlation and alpha cronbach, it was found that 61 items were valid with a reliability of 0.949. This shows in the very high category. It is hoped that BK teachers can use this scale to map the level of self-discipline of junior high school students who are in the high, medium, and low categories.